PENTINGNYA KOMPETENSI PROFESIONAL BAGI MAHASISWA CALON GURU KRISTEN DALAM KEGIATAN PEMBELAJARAN MATEMATIKA [THE IMPORTANCE OF PROFESSIONAL COMPETENCE FOR PRE-SERVICE CHRISTIAN TEACHERS IN MATHEMATICS LEARNING ACTIVITIES] - Ester Putri Febriana; Tanti Listiani; Henni Sitompul (Polyglot, 2021)
Schools are educational institutions that are primarily focused on achieving educational goals. In achieving these goals, schools need competent teachers. Competent teachers are teachers who have four teacher competencies, namely learning management (pedagogical competence), potential development (social competence), academic mastery (professional competence), and personality attitudes (personality competence). A teacher must possess these four teacher competencies in order to support his/her role as an educator. Based on the field experience program conducted by pre-service teachers, it is evident that pre-service teachers lack professional competence. The purpose of writing this paper is to further examine the importance of professional competence for pre-service teachers in supporting the ongoing learning activities at a school, especially for a Christian teacher. The importance of professional competence for a pre-service teacher can provide confidence when teaching, the capacity to guide in mathematics learning activities, and the ability to carry out his/her role as a restoration agent. To improve professional competence, teachers should conduct microteaching activities, study, and attend seminars and other benefical activities.BAHASA INDONESIA ABSTRACT: Sekolah merupakan lembaga pendidikan yang paling utama berfokus kepada pencapaian tujuan-tujuan pendidikan. Dalam mencapai tujuan pendidikan yang telah ditetapkan, sekolah membutuhkan seorang guru yang berkompeten. Guru yang berkompeten adalah guru yang memiliki empat kompetensi guru yaitu pengelolaan pembelajaran (kompetensi pedagogi), pengembangan potensi (kompetensi sosial), penguasaan akademik (kompetensi profesional), dan sikap kepribadian (kompetensi kepribadian). Keempat kompetensi guru tersebut haruslah dimiliki oleh seorang guru agar dapat mendukung perannya sebagai seorang pendidik. Berdasarkan program pengalaman lapangan yang telah dilakukan oleh mahasiswa calon guru, dapat dilihat bahwa mahasiswa calon guru masih kurang dalam kompetensi profesional. Tujuan penulisan paper ini untuk mengkaji tentang pentingnya kompetensi profesional bagi seorang mahasiswa calon guru dalam mendukung kegiatan pembelajaran yang sedang berlangsung di sekolah, terutama dalam diri seorang guru Kristen. Pentingnya kompetensi profesional bagi seorang mahasiswa calon guru, yaitu memberikan rasa percaya diri ketika mengajar, guru dapat menjadi penuntun dalam kegiatan pembelajaran matematika, serta guru dapat menjalankan perannya sebagai agen restorasi. Dalam meningkatkan kompetensi profesional, guru disarankan untuk dapat melakukan kegiatan microteaching, belajar, mengikuti seminar dan kegiatan-kegiatan yang dapat meningkatkan kompetensi tersebut.